EFFECTS OF LEADERSHIP EFFECTIVENESS, ORGANIZATIONAL CULTURE, TEAM COHESIVENESS, AND ORGANIZATIONAL COMMITMENT ON LECTURER ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN IKIP PGRI PONTIANAK -WEST KALIMANTAN - Apriadi, Dedy (JERAM, 2017)
Abstract This study aims to examine the influence of leadership effectiveness, organizational culture, team cohesiveness, and organizational commitment on lecturers Organizational Citizenship Behavior in IKIP PGRI Pontianak in West Kalimantan. The sampling technique using Simple Random Sampling at 150 lecturers in IKIP PGRI Pontianak in West Kalimantan The analytical method used is path analysis. The results showed that the leadership effectiveness, organizational culture, team cohesiveness, and organizational commitment directly impact positively on lecturers Organizational Citizenship Behavior in IKIP PGRI Pontianak in West Kalimantan .  Keywords    Leadership Effectiveness, Organizational Culture, Team Cohesiveness, Organizational Commitment, Organizational Citizenship Behavior